Plan de negocio para la comercialización de cocteles a base de aguardiente-currincho - Rodríguez Daza, Joselyn Jamileth (2021)
Our business plan consists of the distribution of the delicious cocktail based on milk, currincho and fruit pulp, in order to satisfy the needs of our clients. Once the market study is finished, it can be determined that the proposed business is aimed at the public 18 years and older and people who are willing to try a different drink based on natural fruits of excellent quality and without processing. the statement of the problem, the general and specific objectives, justification of the proposal, delimitation of the investigation, methodology and investigation techniques were developed, the correct mechanisms were carried out for the elaboration of the business plan, detailed below; Organizational structure, situational analysis, strategic plan, production and marketing plan and finally the financial study which will allow us to evaluate if the business plan will be viable, as well as determine the approximate time in which the investment is recovered..........